2019
DOI: 10.31557/apjcp.2019.20.6.1803
|View full text |Cite
|
Sign up to set email alerts
|

Eating Habits and Preferences of Polish Women Undergoing Treatment for Breast Cancer

Abstract: Objective:The objective of the study is the assessment of the nutrition as well as the eating habits and preferences of Polish women undergoing breast cancer treatment. Material and methods: The study included women undergoing breast cancer treatment aged over 50 years. Data were collected on 112 respondents, residents of a large city, for whom the average time elapsed since the completion of treatment was 5 years. Their eating habits and preferences were determined on the basis of the frequency of consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Therefore, patients should be encouraged to consume wholegrain products, with preventive actions aimed at changing eating behaviours undertaken, as these products prevent metabolic diseases and cancer. Research by Demuth et al [36] indicate that prophylactic measures against cancer are necessary, both in women diag-nosed with breast cancer and after completed treatment. The study designed to assess the diet and eating habits of Polish women over 50 years of age undergoing breast cancer treatment showed that the eating habits and respondents' preferences regarding compliance with the 'healthy' and 'unhealthy dietary index' (which were determined on the basis of the FFQ questionnaire) were unsatisfactory [36].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients should be encouraged to consume wholegrain products, with preventive actions aimed at changing eating behaviours undertaken, as these products prevent metabolic diseases and cancer. Research by Demuth et al [36] indicate that prophylactic measures against cancer are necessary, both in women diag-nosed with breast cancer and after completed treatment. The study designed to assess the diet and eating habits of Polish women over 50 years of age undergoing breast cancer treatment showed that the eating habits and respondents' preferences regarding compliance with the 'healthy' and 'unhealthy dietary index' (which were determined on the basis of the FFQ questionnaire) were unsatisfactory [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a relationship between diet and disease, and it is important to understand the foods and nutrients that women consume, as well as their dietary habits, to improve their health. [4][5][6][7] Various dietary survey methods are used to determine participantsʼ food intake. Some dietary survey methods measure actual food intake, such as 24-hour food recalls and diet records, while others collect habitual food intake data, such as food intake frequency questionnaires and food history questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Its effect was to kill tumor cells with chemical/natural compounds, but its effect was systemic and it exposed a wide range of side effects (Liu et al, 2021). Therefore, some researchers have proposed to develop creative eating habits with the same therapeutic properties as the reference drug, but with fewer systemic side effects to prevent and limit the malignant transformation of tumors (Demuth & Czerniak, 2019;Rafiq et al, 2018;Gaspar-Pintiliescu et al;, thereby improving the quality of life of breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%